Knowledge, attitude, and practices toward evidence-based dentistry among dentists of Bengaluru city - Uma Shankarachari Rajagopalachari; Manjunath P Puranik; Soni Rajput (Wolters Kluwer Medknow Publications, 2017)
Introduction: In these challenging times, practice of dentistry is becoming more complex. Evidence-based dentistry (EBD) strengthen the profession by identifying knowledge gaps, confidence in clinical decision making and encourage to formulate clear questions regarding the evidence needed. It closes the gap between clinical research and real-world practice and provides tools to interpret and apply research findings. Aim: This study aims to describe the knowledge, attitudes, and practices of dentists toward the concept of EBD. Materials and Methods: A cross-sectional survey was conducted among a representative sample of 300 dentists in dental colleges and private practices of Bengaluru city using a self-administered questionnaire. Descriptive statistics was computed. The frequency for each domain of knowledge, attitude, and practice was calculated after giving weight age for each option. For statistical analysis, t-test was used. P < 0.05 was considered statistically significant. Results: Mean age of the dentists was 32.9 ± 8.1 years. Mean knowledge, attitude, and practice were 17.41 ± 6.45, 1.92 ± 0.75, and 17.06 ± 3.05, respectively. Majority of them relied on their own judgment as a guide to primary care practice. Very less number of dentists relied on Cochrane library as a reliable source for evidence-based practice. Conclusions: Although the dentists were generally aware of the concept of EBD very little use of this concept in clinical practice was followed quoting lack of access as a barrier. However, the reflected attitudes toward EBD were good with most of the respondents expressing an interest in having further education in this concept.